Strengthening Human Capital through Social Capital (A Study on Kacang Tore Small Enterprise) - Rahel Widiawati Kimbal (AIBPM Publisher, 2020)
The objective of this study deals with revealing the component(s) of human capital which functions to establish social capital in the Kacang Tore small enterprises. This study involves peanut farmers and Kacang Tore business owner who are regarded as business doers of small enterprises. The research constitutes a qualitative study by applying triangulation technique of collecting data namely observation, interview, and documentation. The analysis of data follows Spradley’s Developmental Research Sequence. The findings point out that human capital defined as the economic value of human resources relating to ability, knowledge, ideas, innovation, energy, and commitment constitutes the power to establish a strong social capital. Human capital in the small enterprise can be identified in several forms namely 1) individual competence, 2) High work motivation, 3) value system of the work environment, 4) teamwork and 5) leadership in running the small enterprise. These components contribute to build and strengthen the required social capital in the small enterprise such as 1) strong relative network, 2) mutual trust and collaboration, 3) obedience to the norm, 4) mutual exchange of kindness, and 5) meaningful life value. Social capital derived from strong human capital constitutes powerful energy for the survival of the small enterprise amidst the tight competition in the era of industrial revolution 4.0.